Women in toxicology in the United States. Issue 4 (30th July 2021) - Melo, Luma
Abstract: Since the toxicology field was established, women have played a critical role in it. This article is written to celebrate the 20-year anniversary of the Special Interest Group for Women in Toxicology, affiliated with the Society of Toxicology. Six female pioneers in modern Toxicology from different social classes and education backgrounds are featured. Despite these differences, they overcame similar obstacles in gender, politics, and scientific barriers to disseminate their research. This discussion will start with Ellen Swallow Richards, who, besides being the pioneer in sanitary engineering, founded the home economics movement that applied science to the home. The discussion will continue with Alice Hamilton, a contributor to occupational health, a pioneer in the field of industrial toxicology, and an example of generosity to social movements and those in need. Subsequently, the most famous woman we discuss in this paper is Rachel Carson, whose fundamental work in environmental Toxicology is evidenced in her important book Silent Spring . This article also features Elizabeth Miller, a biochemist known for her fundamental research in cancer carcinogenesis, followed by Mary Amdur. Nowadays much of what we know about air pollution comes due to Mary, who paid from her own pocket for her experimental animals to investigate Donora smog pollutants and their health damages. And last but not least Elizabeth Weisburger, a chemist who made significant contributions in carcinogenesis and chemotherapy drugs who worked for 40 years at the National Cancer Institute. Here, we discuss the aforementioned women's careers and personal struggles that transformed toxicology into the field we know now.